Reviving an Indigenous Rainforest Sign Language: Digital Oroo’ Adventure Game - Tariq, Zaman; HHeike, Winschiers-Theophilus; Alvin Wee, Yeo; Lai, Chiu Ting; Garen, Jengan (American Institute of Physics Inc., 2015)
The extinction of indigenous languages, which convey cultural worldviews, remains a continued threat to cultural heritage preservation. The nomadic Penans in the rainforests of Malaysian Borneo, have developed Oroo’, their own forest sign language, to communicate with each other. Yet with recent developments the younger generations are drawn more to technology than engaging with their surrounding forest, only vaguely remembers few signs. In this paper, we present one of our initiatives to reintroduce Oroo’ to the younger Penan generation by digital means. Under the auspices of a long term collaboration with the Long Lamai community we have developed and evaluated a first digital Oroo’ adventure game for the children. Results show a general interest in digital games with indigenous Penan contents albeit with a slight learning curve only. The project efforts rely on local community’s active participation and using indigenous wisdom as an essential component to digitalize and preserve the language further.